Vagal Maneuvers, a Unique Osteopathic Addition to the ACLS Armament: Review - Pescatore II, Richard M.; N. Abo, Benjamin; C. Ruppel, Matthew; M. Smolar, Jessica; M. Sklar, Robert; A. Pulley, Stephen (International Journal of Medical Research and Review, 2015)
In the United States, there are more than half a million people diagnosed with supraventricular tachycardia (SVT). There are approximately 89,000 new presentations of SVT a year, many of them presenting to U.S. emergency centers for initial management of their tachydysrhythmia. The purpose of this article is to describe the wide range of effective techniques for the initial non-pharmacologic management of supraventricular tachycardia, and to discuss their mechanisms of action and potential drawbacks. Additionally, we will introduce a commonly used Osteopathic Manipulative Therapy as a potential first-line treatment option for hemodynamically stable SVT.